Comparative Analysis of Balances of Payments of Ukraine and Poland in the Post-crisis Economic Environment - LYPKO, Nazariy (Journal of Advanced Research in Law and Economics; Vol 4 No 2 (2013): JARLE Volume IV Issue 2(8) Winter 2013, 2016)
Condition of balance of payments is a crucial factor for effective development of small open economies, such as Poland and Ukraine. Because of their dependence on situation on international markets, Poland and Ukraine are really vulnerable to fluctuations of global conjuncture. That is why it is essential to develop effective instruments of balances of payments adjustment for both national economies under consideration. Such need requires research of the main regularities in the process of balance of payments adjustment for developing countries, since not all the aspects have been already explored. A comparative analysis of the balances of payments of these countries is conducted in the article. The article aims to prove similarities in external areas of both countries and explain why Poland has reached higher success in the process of overcoming the consequences of the global financial crisis. Such conclusions can be used as a roadmap for Ukraine on its way to adjustment of balance of payments. The main reason for such exploration is that Ukraine’s balance of payments is still in deficit conditions and negatively affects the overall state of national economy of the country.
Keywords: balance of payments; current account; capital account; small open economy; adjustment of balance of payments